The Culture of Flexing in the Context of the Maqāṣid al-Qur’an: A Case Study of Social Media - Raden Kurnia Kholiska; Muhammad Ali Fuadi; Sukron Azhari; Vijay Asyfa Betay Seer; Mohammad Abdul Aziz (International Journal of Sociology of Religion, 2025)
This article discusses the maqasid behind the “flexing” verses, as these five verses do not explicitly prohibit flexing as a promotional strategy. Meanwhile, in the present day, the proliferation of flexing content on social media serves as a promotional strategy to generate income. This issue is significant for reinterpreting the flexing verses so that they can address contemporary challenges and be considered in all aspects. Therefore, maqasidi exegesis is employed as an analytical tool to uncover the maqasid of the flexing verses and to identify the benefits and harms of flexing content on social media. Findings from this study: Flexing, taken literally, does not merely mention the prohibition of flexing during prayer and charity but encompasses all activities (both ritual and non-ritual acts of worship). Meanwhile, the maqasid behind the prohibition of flexing are to protect the religion (from hypocrisy, disbelief, and polytheism) and to protect the soul (from showing off, arrogance, and seeking fame). Based on an assessment of the benefits and harms of flexing content on social media, flexing as a promotional strategy is not permitted because it tends to be harmful to both oneself and others.